Controlling angiogenesis in gastric cancer: A systematic review of anti-angiogenic trials. Issue 2 (1st October 2016) - Shan, Fei; Miao, Rulin; Xue, Kan; Li, Zhemin; Li, Ziyu; Bu, Zhaode; Wu, Aiwen; Zhang, Lianhai; Wu, Xiaojiang; Zong, Xianglong; Wang, Xiaohong; Li, Shuangxi; et al.
Highlights: Most anti-angiogenic agents are reported to improve in response rate, but not progression-free survival or overall survival compared to chemotherapy alone. Only ramucirumab has been demonstrated to improve outcome as secondary-line treatment in advance gastric cancer. Searching robust biological predictors (biomarkers) to stratify patients. Abstract: Purpose: Angiogenesis is a promising therapeutic target to inhibit tumor growth. This review summarizes data from clinical trials of anti-angiogenic agents in gastric cancer. Design: A systematic search of PubMed, Embase and conference databases is performed to identify clinical trials with specific anti-angiogenic agents in gastric cancer treatment Results: The risk of disease progression (37–52%) and death (19–22%) with ramucirumab as second-line treatment decreases in phase III trials in advanced gastric cancer. No significant improvement in overall survival (OS) with the addition of bevacizumab to chemotherapy is shown. Bevacizumab or ramucirumab combined with traditional chemotherapy is associated with higher adverse event rate compared to chemotherapy alone. Except for apatinib, phase II trials of other tyrosine kinase inhibitors (TKIs) may improve overall response rate, but there are no significant improvements in OS and progression-free survival (PFS) when combined with chemotherapy. Conclusion: Phase III trials in advanced gastric cancer have demonstrated improved outcome with ramucirumab as second-line treatment. Most of the other studies on anti-angiogenic agents in gastric cancer have reported improvement in response rate but not in OS compared to chemotherapy alone. Future research is expected in optimizing the anti-angiogenic therapy combined with traditional treatment.